Synthesis and biological evaluation of santacruzamate A and analogs as potential anticancer agents. Issue 2 (2nd December 2014) - Liu, Qi; Lu, Wenhua; Ma, Mingzhe; Liao, Jianwei; Ganesan, A.; Hu, Yumin; Wen, Shijun; Huang, Peng
Abstract : After a SAR study of santacruzamate A, 5 was discovered to selectively inhibit the growth of malignant cancer cells. Abstract : Santacruzamate A, a recently discovered natural product from a Panamanian marine cyanobacterium Symploca sp., features a similar structure to the clinically used histone deacetylase (HDAC) inhibitor vorinostat (SAHA ). We have synthesized the natural product and a small set of analogues for SAR studies. To our surprise, the synthetic natural product santacruzamate A (1a ) and the analogues did not show an obvious inhibition even at 2 μM in HDAC enzyme assays while the IC50 value was 0.12 nM in the original report. However, a novel compound, 5, containing a terminal thiourea motif was found to inhibit the growth of malignant cells at submicromolar concentrations. Moreover, 5 was not cytotoxic to normal human colonic epithelial cells CCD841, suggesting that its cytotoxicity was specific to cancer cells. Further investigation indicated that the compound induced apoptosis, affected cell cycle progression and increased ROS production. We believe its mechanism of action is unrelated to HDAC inhibition and the original activity reported for santacruzamate needs to be reevaluated.